TINJAUAN YURIDIS PENGGUNAAN FRASA “ORANG LAIN ATAU SUATU KORPORASI” YANG MERUGIKAN SALAH SATU PIHAK BERDASARKAN PUTUSAN MK NOMOR 25/PUU-XIV/2016 TENTANG TINDAK PIDANA KORUPSI - Bagaskara Dwi Wardhani; Zulfikar Jayakusuma; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In Law Number 20 Year 2001 states that the phrase or other person or a corporation in Article 2 paragraph (1) and Article 3 of the Corruption Act, is very detrimental and / or potentially detrimental to the applicant, who in carrying out their duties and His authority in government positions in regional government, cannot avoid the act of issuing decisions, especially in terms of determining the implementation of government projects, certainly benefits others or a corporation. There is no individual or corporation that is willing to carry out what government project work if it does not bring profit to him, because they are entrepreneurs who work for profit. This research is limited to two problem formulations, First, How is the juridical analysis of the use of the phrase